Main problems in the development and provision of personalized electronic training content - Blagoev, Ivaylo; Monov, Vladimir; Vassileva, Gergana (Yearbook Telecommunications, 2019)
The aim of this article is addressing of the main issues with today's software solutions for developing interactive learning content. As a result, the main approaches are derived to providing adaptive personalized training are outlined and the key problems in creating personalized interactive e-learning are systematized.